2021
DOI: 10.1002/slct.202102997
|View full text |Cite
|
Sign up to set email alerts
|

Hydroisomerization with a Hierarchical SAPO‐11 Supported Ni Catalyst: Effect of DTAB Content[]**

Abstract: In order to explore the effect of the amount of mesoporous template on the physicochemical properties and hydroisomerization of the hierarchical SAPO‐11, a series of hierarchical SAPO‐11 were synthesized by adding different amounts of dodecyl trimethyl ammonium bromide(DTAB) as mesopore structure directing agent. The synthesized hierarchical SAPO‐11 were characterized by XRD, N2 adsorption‐desorption, SEM, TEM, NH3‐TPD and Py‐FTIR. The results showed that the addition amount of DTAB had a significant effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Another important method to introduce hierarchically porous structure into SAPO-11 is the so-called templating synthesis. Besides carbon black and metal–organic framework, the long-chained molecules were chosen as the templating agent to synthesize SAPO-11 molecular sieve, and the mesopore width can be modulated by varying their chain lengths . Unfortunately, their relatively high cost and unclear assembly behaviors at high temperatures limit their wide applications as mesoporogen.…”
Section: Introductionmentioning
confidence: 99%
“…Another important method to introduce hierarchically porous structure into SAPO-11 is the so-called templating synthesis. Besides carbon black and metal–organic framework, the long-chained molecules were chosen as the templating agent to synthesize SAPO-11 molecular sieve, and the mesopore width can be modulated by varying their chain lengths . Unfortunately, their relatively high cost and unclear assembly behaviors at high temperatures limit their wide applications as mesoporogen.…”
Section: Introductionmentioning
confidence: 99%
“…5,16–21 Recent research has demonstrated that the introduction of mesopores into SAPO-11 molecular sieves and the construction of a micropore-mesoporous hierarchical pore structure could effectively alleviate the diffusion limitation, reduce the selectivity of cracked products and improve the selectivity of isomers. 22–26 For example, Wen et al 22 reported that the Pt/SAPO-11 catalyst prepared with hierarchical SAPO-11 molecular sieves as a carrier has higher double-branched isomerization selectivity and lower cracking selectivity than the conventional microporous SAPO-11 molecular sieve in the hydroisomerization of alkanes. Zhang et al 27 pointed out that hierarchical SAPO-11 can increase the number of pore active sites in the hydroisomerization compared to the conventional SAPO-11, which is conducive to the formation of isomers and avoids the cracking of the generated isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, long-chain alkyl trimethyl ammonium bromides (C n H 2 n +1 (CH 3 ) 3 NBr) are often used as mesoporogens in the synthesis of hierarchical SAPO-11 molecular sieves. 5,13,25,27,38–40 Unfortunately, how the alkyl chain length of the mesoporogen affects the physicochemical properties and catalytic performance of hierarchical SAPO-11 molecular sieves has not been systematically investigated. In this study, hierarchical SAPO-11 molecular sieves will be synthesized by using n -alkyltrimethylammonium bromides with different alkyl chain lengths from C 8 to C 16 as mesoporogens and analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), N 2 adsorption–desorption, transmission electron microscopy (TEM), NH 3 temperature-programmed desorption (NH 3 -TPD) and pyridine adsorption Fourier-transform infrared (Py-IR).…”
Section: Introductionmentioning
confidence: 99%